2008
DOI: 10.1007/s10616-008-9147-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and melatonin 1a receptor distribution in the ovaries of African ostrich chicks

Abstract: Healthy 90-day-old ostrich chicks were used in the present study. The ultrastructure and melatonin 1a receptor (MT1) distribution in the ovaries of ostrich chicks was observed by transmission electron microscope and light microscope. The results showed that the ostrich chick ovary contained primordial follicles, primary follicles and secondary follicles, but no mature follicles. There are some unique ultrastructural characteristics observed in the secondary follicle, such as the cortical granule, which was loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The antigonadal effects of melatonin has also been reported in Oryzias latipes ( Uraski, 1972 ), and Heteropneustes fossilis ( Sundararaj and Keshavanath, 1976 ). The effect of MLT on the structure of ovary and ovarian cells was similar as reported earlier ( Borg and Ekstrom, 1981 ; Fatemet et al, 2007 ; Wang et al, 2008 ). The minimum employed dose of melatonin was 25 μg/100 g body weight/day, and this is frequently reported dose to study the effect of melatonin on the gonads ( Maitra et al, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
“…The antigonadal effects of melatonin has also been reported in Oryzias latipes ( Uraski, 1972 ), and Heteropneustes fossilis ( Sundararaj and Keshavanath, 1976 ). The effect of MLT on the structure of ovary and ovarian cells was similar as reported earlier ( Borg and Ekstrom, 1981 ; Fatemet et al, 2007 ; Wang et al, 2008 ). The minimum employed dose of melatonin was 25 μg/100 g body weight/day, and this is frequently reported dose to study the effect of melatonin on the gonads ( Maitra et al, 2005 ).…”
Section: Discussionsupporting
confidence: 89%
“…Melatonin regulates ovarian function through activation of multiple receptors and signaling pathways on different target cell types especially theca and granulosa cells (Wang et al, 2008). The binding site in the chicken ovary is located in the follicular cell layer (Ayre et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few studies about the polymorphism of MTNRIB . Interestingly, some studies in birds found that melatonin receptor subtypes were identified in ovaries (He et al., 2014; Sundaresan et al., 2009; Wang et al., 2008), which indicated that melatonin may directly affect ovarian function through activating of its receptors. For example, the expression levels of MTNR1A, MTNR1B and MTNR1C initially increased and later decreased during the follicular development cycle in geese, suggested that melatonin receptors participated in activating small follicles to develop into subsequent higher hierarchical follicles (He et al., 2014).…”
Section: Introductionmentioning
confidence: 99%